Analysis Of the Youth Part of World Politicians - Burkhonov Shahzod Burkhon o’g’li (Zien Journals, 2021)
This article identifies the characteristics of youth organizations, their main features and specifics of their activities as modern factors of world politics, the main problems and contradictions that arise in the process of their activities, as well as the main prospects for their development
Keywords: state youth policy; implementation; concept; globalization